HUBUNGAN KUALITAS FISIK RUMAH TERHADAP KEJADIAN ISPA PASCA BENCANA ERUPSI GUNUNG SINABUNG DI WILAYAH KERJA PUSKESMAS KECAMATAN TIGANDERKET KARO SUMATERA UTARA PADA TAHUN 2015 - desi marianta; indra chahaya; irnawati marsaulina (Lingkungan dan Kesehatan Kerja, 2015)
Abstract Tiganderket sub-district is one of the districts that were less than 10 km from Mount Sinabung that erupted since 2010 until now. The problem in this research is the increasing cases of Acute Respiratory Infection (ARI) in the Primary Health Care (PHC) Tiganderket sub-district in 2014. The purpose of this study was to determine the relation between the physical quality of houses with ARI incidents after eruption of Mount Sinabung in the PHC Tiganderket sub-district Karo Sumatera Utara in 2015. This study is observational analytic study with case control study design. The population is suffering from ARI and was treated at the PHC Tiganderket during 2014 as many as 3,504 people, with a sample of 124 peoples were obtained by proportional random sampling. Data were analyzed with Chi Square test statistic 95% CI (p = 0,05) and Odds Ratio value. Based on the results of research in the Puskesmas Tiganderket sub-district concluded respondent characteristics related to ARI is a job (p value = 0,010). Physical conditions related to the ARI is the condition of the floor (p value = 0,000, OR = 5,697). Occupant behavior characteristics related to ARI is to open a window every day (p value = 0,001, OR = 3,838) and smoking (p value = 0,000, OR = 7,091). There is no relation between age (p value = 1,000), sex (p value = 0,463), marital status (p value = 1,000), education (p value = 0,407), village address (p value = 1,000), spacious room ventilation (p value = 0,769), type of wall (p value = 0,402), room air humidity (p value = 0, 15), room temperature, room density (p value = 0,094), the occupants sweep the house every day (p value = 0,697 , OR = 0,737), mop the house every week (p value = 0,243) with ARI in the PHC Tiganderket sub-district. It is suggested to the community to keeping house clean, opening the windows only in the morning, avoiding smoking inside the house, and using mask when outside the house